Bioethanol production from cellulosic hydrolysates by engineered industrial Saccharomyces cerevisiae. (March 2017) - Lee, Ye-Gi; Jin, Yong-Su; Cha, Young-Lok; Seo, Jin-Ho
Highlights: Industrial Saccharomyces cerevisiae was able to edit genome by CRISPR-Cas9. A xylose assimilating pathway was introduced into an industrial yeast strain. Expression of NADH oxidase improved the bioethanol productivity. The concentration of ethanol produced by silver grass hydrolysates is 55.51 g/L. Abstract: Even though industrial yeast strains exhibit numerous advantageous traits for the production of bioethanol, their genetic manipulation has been limited. This study demonstrates that an industrial polyploidy Saccharomyces cerevisiae JHS200 can be engineered through Cas9 (CRISPR associated protein 9)-based genome editing. Specifically, we generated auxotrophic mutants and introduced a xylose metabolic pathway into the auxotrophic mutants. As expected, the engineered strain (JX123) enhanced ethanol production from cellulosic hydrolysates as compared to other engineered haploid strains. However, the JX123 strain produced substantial amounts of xylitol as a by-product during xylose fermentation. Hypothesizing that the xylitol accumulation might be caused by intracellular redox imbalance from cofactor difference, the NADH oxidase from Lactococcus lactis was introduced into the JX123 strain. The resulting strain (JX123_noxE) not only produced more ethanol, but also produced xylitol less than the JX123 strain. These results suggest that industrial polyploidy yeast can be modified for producing biofuels and chemicals.